Распределительные устройства среднего напряжения 6-35 КВ с элегазовой изоляцией - Гречко, А.М. (Електротехніка і електромеханіка, 2011)
The article gives a constructions' analytic review of modern SF6 switchgear for average voltage 6-35 kV.